Exploring Pitch Accent as an Element of Fluency in L2 English Academic Presentations – a Proficiency-based Sampling Report - Klimczak-Pawlak, Agata; Waniek-Klimczak, Ewa (Research in Language, 2023)
The study explores the effectiveness of raising prosodic awareness in teaching academic presentations to a mixed proficiency group of adult Polish students majoring in English from the perspective of prosody as well as utterance fluency measures. A 15-week course included a 4-week prosody practice with focus on pausing and pitch accent. In the course students produced two speeches of approximately the same length: an impromptu before the practice and a prepared presentation after the practice. The speeches were recorded and analysed for the number of pitch accents and pauses. The data for three students, representing different general L2 proficiency levels are discussed in this paper. The results of prosodic performance operationalized as the pause to pitch accent ratio show the greatest benefit of prosody training in the case of the lowest proficiency level student. The analysis of selected utterance fluency measures shows a positive effect of prosody practice across speakers, providing additional support for the relevance of pitch accent in academic presentations in L2. The study has theoretical and practical implications, as it suggests the need to include pitch accent/pause proportion in utterance fluency measures in fluency studies as well as in pedagogical practice.